Frailty assessment scales for the elderly and their application in primary care: A systematic literature review - Dolenc Eva; Rotar-Pavlič Danica (Sciendo, 2019)
The increase in the elderly population is causing changes and challenges that demand a comprehensive public health response. A specific characteristic of the elderly is their frailty. Today's problems with identifying levels of frailty are being resolved by numerous tools in the form of frailty assessment scales. This systematic review establishes which frailty assessment scales for the elderly are being used and what their applicability in primary care is like in Slovenia and around the world.